The Study Of Henna Leaves Extract As Green Corrosion Inhibitor For Mild Steel In Acetic Acid - Chaudhari, H.g.; Vashi, R.t. (University of Eloued جامعة الوادي, 2016)
The inhibitive action of henna leaves extract on mild steel in acetic acid solution have been investigated by weight-loss, A C impedence and potentiodynamic polarization measurements. The study indicates that as acid concentration increases corrosion rate increases. The corrosion inhibition efficiency increases with increase in concentration of extract. The result obtained revealed that henna leaves extract act as efficient inhibitor. The adsorption of the henna leaves extract obeyed Langmuir adsorption isotherm. The calculated thermodynamic parameters indicated that the adsorption was a spontaneous, exothermic process accompanied by an increase in entropy. Cathodic and anodic polarization curves show that henna leaves extract is a mixed-type inhibitor.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: corrosion; mild steel; acetic acid; henna leaves extract; green inhibitor.